My day at school - Law, Felicia (G. Stevens Pub. Milwaukee, 1986)
Text and illustrations present the variety of activities and events that a child encounters during a school day.
Grade level : 2 - 3
Keywords: Readers (Primary); School adjustment -- Juvenile literature